2020
DOI: 10.1186/s12911-020-01252-5
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Meta-analysis of contrast-enhanced ultrasound and contrast-enhanced harmonic endoscopic ultrasound for the diagnosis of gallbladder malignancy

Abstract: Background The diagnosis between benign and malignant gallbladder lesions is sometimes difficult. The objective of this study is to assess whether contrast-enhanced ultrasound (CEUS) and contrast-enhanced harmonic endoscopic ultrasound (CH-EUS) can be an accurate method for detecting gallbladder malignancy and to determine which imaging signs can be indicative of malignancy. Methods A study search of PubMed, Elsevier, and Sciencedire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Therefore, assessment of microvessels can provide valuable information that discriminates mural nodules from mucous clots in IPMN and gallbladder lesions from gallbladder sludge. Several studies report the utility of CE-EUS for differential diagnoses based on vascular assessment in pancreatobiliary diseases [11][12][13][14][15][16][17][18]. Here, we found that DFI-EUS (100%) was significantly superior to e-FLOW EUS (64%) for differential diagnosis with detecting vascularity.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Therefore, assessment of microvessels can provide valuable information that discriminates mural nodules from mucous clots in IPMN and gallbladder lesions from gallbladder sludge. Several studies report the utility of CE-EUS for differential diagnoses based on vascular assessment in pancreatobiliary diseases [11][12][13][14][15][16][17][18]. Here, we found that DFI-EUS (100%) was significantly superior to e-FLOW EUS (64%) for differential diagnosis with detecting vascularity.…”
Section: Discussionmentioning
confidence: 60%
“…Contrast-enhanced EUS (CE-EUS) increases the detectability of vessels and can overcome some of these limitations. Indeed, many studies demonstrate the utility of CE-EUS for diagnosis of pancreatobiliary lesions [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]; thus, the technique is used widely in the clinic. However, there are some problems.…”
Section: Introductionmentioning
confidence: 99%
“…CEUS may provide more useful information and improve diagnostic efficiency for gallbladder lesions than conventional ultrasound modalities ( 5 ) . CEUS is a promising imaging modality, with a high sensitivity for distinguishing gallbladder adenoma from adenocarcinoma ( 6 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Xue Liang and Xiang Jing [56] reported a meta-analysis of contrast-enhanced ultrasound and contrast-enhanced harmonic EUS (CH-EUS) for the diagnosis of GB malignancy. The pooled sensitivities of CH-EUS and specificities were 0.92 and 0.89 (Table 6), respectively, in this meta-analysis.…”
Section: Contrast-enhanced Eusmentioning
confidence: 99%